2018
DOI: 10.1073/pnas.1801247115
|View full text |Cite
|
Sign up to set email alerts
|

Coupling MALDI-TOF mass spectrometry protein and specialized metabolite analyses to rapidly discriminate bacterial function

Abstract: SignificanceMass spectrometry is a powerful technique that has been used to identify bacteria by their protein content and to assess bacterial functional traits through analysis of their specialized metabolites. However, until now these analyses have operated independently, which has resulted in the inability to rapidly connect bacterial phylogenetic identity with potential environmental function. To bridge this gap, we designed a MALDI-TOF mass spectrometry data acquisition and bioinformatics pipeline (IDBac)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 41 publications
1
82
0
1
Order By: Relevance
“…Library isolates were prepared for bioinformatics analysis using IDBac, a matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry pipeline that allows for rapid analysis of microbial proteins and specialized metabolites. 17,20 The standard IDBac workflow uses a 70% aqueous formic acid solution to lyse cells but we found that this procedure was not efficient at lysing the more mucoid bacterial colonies isolated. 20 A trifluoroacetic acid (TFA) extraction prior to plating samples for analysis was the most effective method to consistently collect viable MS fingerprint profiles for IDBac analysis.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Library isolates were prepared for bioinformatics analysis using IDBac, a matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry pipeline that allows for rapid analysis of microbial proteins and specialized metabolites. 17,20 The standard IDBac workflow uses a 70% aqueous formic acid solution to lyse cells but we found that this procedure was not efficient at lysing the more mucoid bacterial colonies isolated. 20 A trifluoroacetic acid (TFA) extraction prior to plating samples for analysis was the most effective method to consistently collect viable MS fingerprint profiles for IDBac analysis.…”
Section: Resultsmentioning
confidence: 94%
“…21 Measuring proteins in the 3,000 to 15,000 Da range, IDBac organized the microbial isolates into a pseudo-phylogeny dendrogram based on MS fingerprint protein similarity. 17 Figure 2 highlights 82 of the 118 bacterial isolates from our library. 16S rRNA sequencing was performed on a subset of isolates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 However, there is a paucity of information about the metabolic profiles of genetically resistant bacterial populations. 13,14 The data need further screening against METLIN database. 11,12 However, mass-spectrometric data sets depend on CAMERA for compound spectra extraction and annotation.…”
mentioning
confidence: 99%